2012
DOI: 10.1093/annonc/mds060
|View full text |Cite
|
Sign up to set email alerts
|

First-line treatment of advanced ovarian cancer with paclitaxel/carboplatin with or without epirubicin (TEC versus TC)—a gynecologic cancer intergroup study of the NSGO, EORTC GCG and NCIC CTG

Abstract: The addition of epirubicin to standard carboplatin and paclitaxel treatment did not improve survival in patients with advanced ovarian, tubal or peritoneal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 16 publications
3
20
0
Order By: Relevance
“…According to our NMA SUCRA values, PC produced better outcomes with regard to CR, PD and DCR, while DC was more effective regarding ORR and PC + Epirubicin had a higher efficacy in terms of DCR. These results are consistent with previous studies [26, 37, 38], demonstrating there was no efficacy difference between PC, PC + Epirubicin, and DC. However, some studies indicated that toxicity was lower in PC as compared to PC + Epirubicin [37], PC + Topotecan [38], and DC [26].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…According to our NMA SUCRA values, PC produced better outcomes with regard to CR, PD and DCR, while DC was more effective regarding ORR and PC + Epirubicin had a higher efficacy in terms of DCR. These results are consistent with previous studies [26, 37, 38], demonstrating there was no efficacy difference between PC, PC + Epirubicin, and DC. However, some studies indicated that toxicity was lower in PC as compared to PC + Epirubicin [37], PC + Topotecan [38], and DC [26].…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with previous studies [26, 37, 38], demonstrating there was no efficacy difference between PC, PC + Epirubicin, and DC. However, some studies indicated that toxicity was lower in PC as compared to PC + Epirubicin [37], PC + Topotecan [38], and DC [26]. Epirubicin inhibits DNA and RNA synthesis by intercalating DNA strands [7] and Topotecan inhibits cancer cell differentiation through PPARγ degradation [12], which disturbs the normal processes of cell division and differentiation, and impedes cell damage repair,.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In Japan, approximately 7,000 cases of EOC are diagnosed every year, and an estimated 4,467 women died of this disease in 2007 [1]. Despite the use of advanced strategic therapies, including surgery and chemotherapy, the 5-year overall survival (OS) rate is approximately 30% [2,3,4,5]. EOC accounts for approximately 90% of ovarian malignancies, and it is commonly diagnosed at a menopausal age.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, although TRAIL is well tolerated in patients, its single-agent efficacy is very limited and not all tumor cell lines respond well (20,21). Paclitaxel has emerged as the first-line therapy for EOC or recurrent EOC, however, its clinical application is usually limited by the dose-dependent toxicity and development of drug resistance (22,23). Therefore, combination chemotherapy is usually required to achieve efficacy at tolerable dosages.…”
Section: Discussionmentioning
confidence: 99%